Encapsulated OSB Energy Absorption Potential: A Preliminary Analysis (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The transport of radioactive substances is, in many ways, necessary in the context of the nuclear fuel cycle that aims to generate energy or radioisotopes. In the event of a possible accident, the shock-absorbing parts reduce the mechanical stresses on the other components of the transport packaging, since a large part of the kinetic energy is absorbed by the shock absorber. To standardize the design of the research reactor spent fuel assembly transport devices by numerical analysis, a set of dynamic simulations of a benchmark was conducted to representatively capture the phenomena found in the drop tests used in project qualifications. This study aims to present a comparison of different ways of applying wood and wood composites as a useful and accessible impact-absorbing material. The necessary numerical modelling characteristics are validated and the phenomena present in non-isotropic materials are discussed. This study demonstrates the application of material models where energy absorption is the main structural function. In this case, the orientation of the wood fibers became sensitive with an approximate difference of 10% more in the impact absorption potential, without considerable variation in the duration interval of the maximum deceleration.